Combined spinal-epidural analgesia and epidural analgesia induced maternal fever with a similar timing during labor-A randomized controlled clinical trial - Chu, Qinjun; Sun, Yan; Bai, Lihui; Bai, Yafan; Zhang, Dongqing; Zheng, Ping; Jin, Xiaogao (Frontiers in Medicine, 2022)
Background Both epidural and combined spinal-epidural (EA and CSEA) analgesia can induce intrapartum maternal fever. CSEA has a more rapid onset and wider nerve block than EA. Therefore, CSEA might have a different profile of intrapartum maternal fever, including higher temperatures or earlier occurrence. This randomized clinical trial was to determine whether CSEA could cause maternal fever earlier than EA. Methods A randomized, double-blind, controlled clinical trial was performed on 233 nulliparous full-term pregnant women during vaginal delivery. The pregnant women were randomly allocated into the EA group (n = 113) and the CSEA group (n = 120). The fever latent period, from analgesia start to fever occurrence, was the primary endpoint in this study. The temperature was measured every 30 min using an eardrum thermometer during labor analgesia. The fever was defined as an eardrum temperature of ≥38 °C. Results No difference was found in the maternal fever rate between the EA and the CSEA groups (10/113 vs. 7/120, P = 0.356). There was no significant difference in the fever latent period between the two groups (4.75 ± 0.86 h vs. 3.79 ± 2.2 h, p = 0.305). The temperatures at all points had no differences between EA and CSEA. Conclusion CSEA had a similar latent fever period as EA. A further study is warranted to confirm the similar characteristic between CSEA and EA in the development of intrapartum maternal fever. Clinical trial registration www.chictr.org.cn, identifier ChiCTR2000038793.